The effect of green tea extract on indices of liver damage (ALT and AST) caused by high intensity interval training in professional soccer players - Zahra Mansoori; Najmeh kiani; Farhad Daryanoosh; Mahdi Samadi; Vahid Hadidi; Afsaneh Haghdel (Shahid Beheshti University, 2018)
Purpose: high intensity interval training (HIIT) can damage liver. can green tea extract, as an antioxidant,reduce this liver damage? The aim of this study was to investigate the effects of green tea supplementationon two enzymes ALT and AST as indices of liver damage after high-intensity interval training on professionalsoccer players.Methods: Sixteen soccer players were divided into two groups in a quasi-experimental design with repeatedmeasurements. Test on two occasions, and in each Blood, samples were collected 5 minutes before and 24hours after performing the test. The training program included running with high intensity and 2 min restbetween each activity. After 14 days, Conditions was repeated with the exception that a placebo groupconsumed green tea supplement in this stage. The data were analyzed using paired t-test to determinedifferences between groups.Results: The statistical results showed, AST enzyme in supplement group immediately and 24 hours afterexercise was significantly lower than the placebo group (respectively (p=0.001) and (p=0.02)). ALT enzymealso in supplement group immediately after exercise had a much lower dose compared with the placebogroup (p=0.012) but ALT enzyme no significant difference was observed 24 hours after the activity.Conclusions: Based on the significance of the results it seems that green tea extract would reduce the indicesof liver damage after high intensity interval training.